Prediksi Daerah Potensial Penangkapan Ikan Pelagis Besar di Daerah Kabupaten Mamuju - Safruddin Safruddin; Mukti Zainuddin; Chair Rani (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
Large pelagic species such as tuna are known to be abundant in Mamuju Waters,  Makassar Strait.  The distribution and abundance of the fish in that area are expected to be  related to the distributions of sea surface temperature and chlorophyll-a concentration. This study aims to predict spatial and temporal distribution of the species during the period of June 2013-May 2014.  Probability indices used for detection of tuna potential fishing zones (PFZs) were constructed from a model of satellite-based SST and chlorophyll data in relation to tuna fishery. Results showed that the occurrence of tuna species in Mamuju Water were mostly predicted in areas of 118°12’-118°48’ E 1°48’ – 2°30’S with the total area of approximately 7,495 km2.   The potential fishing zones were mainly found in August.  It was likely that tuna potential fishing zones associated with the preferred oceanographic factors throughout the study area.